2020
DOI: 10.1134/s002626172003008x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Magnetotactic Bacteria in the Freshwater Lake Beloe Bordukovskoe, Russia

Abstract: According to 16S rRNA gene-or genome-based phylogeny, magnetotactic bacteria (MTB) belong to diverse taxonomic groups. Here we analyzed the diversity of MTB in a sample taken from the freshwater lake Beloe Bordukovskoe near Moscow, Russia, by using molecular identification based on sequencing of the 16S rRNA gene and mamK, a specific marker gene for these bacteria. A protein encoded by the mamK gene is involved in magnetosome chain arrangement inside the cell. As a result, six operational taxonomic units (OTUs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The genome tree includes 36 previously reported draft genomes of Nitrospirae MTB as of October 2020 and 130 representative non-MTB Nitrospirae genomes. The majority of Nitrospirae MTB genomes are from freshwater lakes (Lin et al, 2014b(Lin et al, , 2017b(Lin et al, , 2018(Lin et al, , 2020bKolinko et al, 2016;Koziaeva et al, 2020;Uzun et al, 2020) and acidic peatland soils (Lin et al, 2020b) with one genome (Nitrospirae bacterium SG8_35_4) from a sulfate-rich zone estuary (Lin et al, 2017a) and one (Nitrospirae bacterium MAG_10313_ntr_31) from a hot spring (Uzun et al, 2020). The average estimated completeness and contamination of available Nitrospirae MTB genomes was 87.35 ± 12.69% and 3.08 ± 6.15%, respectively.…”
Section: Phylogenomic Analysis Of Magnetotactic Nitrospiraementioning
confidence: 99%
See 1 more Smart Citation
“…The genome tree includes 36 previously reported draft genomes of Nitrospirae MTB as of October 2020 and 130 representative non-MTB Nitrospirae genomes. The majority of Nitrospirae MTB genomes are from freshwater lakes (Lin et al, 2014b(Lin et al, , 2017b(Lin et al, , 2018(Lin et al, , 2020bKolinko et al, 2016;Koziaeva et al, 2020;Uzun et al, 2020) and acidic peatland soils (Lin et al, 2020b) with one genome (Nitrospirae bacterium SG8_35_4) from a sulfate-rich zone estuary (Lin et al, 2017a) and one (Nitrospirae bacterium MAG_10313_ntr_31) from a hot spring (Uzun et al, 2020). The average estimated completeness and contamination of available Nitrospirae MTB genomes was 87.35 ± 12.69% and 3.08 ± 6.15%, respectively.…”
Section: Phylogenomic Analysis Of Magnetotactic Nitrospiraementioning
confidence: 99%
“…Recently, since the first report of a nearly complete draft genome of Candidatus (Ca.) Magnetobacterium casensis through a targeted metagenomic approach (Lin et al, 2014b), a growing number of Nitrospirae MTB genomes have been reconstructed from distinct ecosystems through applications of genome-resolved metagenomics (Lin et al, 2017b(Lin et al, , 2018(Lin et al, , 2020bKoziaeva et al, 2020;Uzun et al, 2020) and single-cell genomics (Kolinko et al, 2016). Genomic analyses of Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of marine clays from the western part of Crete [147] and the Pacific Ocean [148], deep-sea sediments from the Atlantic [149] and Pacific [150,151] oceans and the Black Sea [152], microbial mats [153] and sapropels of the Baltic Sea [154], stromatolites in coastal waters [155], sediments from freshwater lakes and rivers of central Russia [156], stratified ferruginous lakes [57] and a Cisalpine lake [157] have shown that single-domain mag-netite or greigite from MTB is a major carrier of stable remanent magnetization in these rocks. Methods used for the analysis included thermal and alternating field demagnetization of natural remanent magnetization, measurement of hysteresis loops, and curves of isothermal saturation remanent magnetization and anhysteretic remanent magnetization.…”
Section: Magnetofossils and Their Propertiesmentioning
confidence: 99%
“…Previously, the man genes were associated only with MTB from the Nitrospirae. Another two MAGs were affiliated with the Syntrophobacteraceae family, where MTB were discovered previously 41 . This is further evidence that binning was conducted correctly and that MTB representatives are indeed present in this family.…”
Section: The Search For Magnetosome Biomineralization Genes In Open Dmentioning
confidence: 99%